1983
DOI: 10.1021/bi00291a009
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-19 nuclear magnetic resonance studies of lipid fatty acyl chain order and dynamics in Acholeplasma laidlawii B membranes. Effects of methyl-branch substitution and of trans unsaturation upon membrane acyl-chain orientational order

Abstract: The hydrocarbon-chain orientational order parameters of membranes of Acholeplasma laidlawii B enriched with straight-chain saturated, methyl iso-branched, methyl anteiso-branched, or trans-unsaturated fatty acids have been determined via fluorine-19 nuclear magnetic resonance spectroscopy (19F NMR). A theoretical description of the 19F NMR spectral line shape is presented that permits the determination of the orientational order parameters associated with specifically monofluorinated palmitic acid probes biosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 20 publications
10
46
0
Order By: Relevance
“…It is possible that the specific effects of acyl chain structure on the La/Hn transition to PEs (i.e., those effects not attributable to changes in acyl chain length and the L8/La phase transition temperature) may be attributable to small differences in the packing energy of the chains and/or to differences in the temperature-dependent changes in the dynamic properties of the liquid-crystalline lipid bilayer. It has been shown previously that acyl chain substitutions of the types described in these studies can have significant effects on the packing properties of the liquid-crystalline state of lipid bilayers (MacDonald et al, 1983(MacDonald et al, , 1984(MacDonald et al, , 1985aSuzuki & Cadenhead, 1985; Rice et al, 1987;Balthasar et al, 1988). In fact, the interpretation of such data implicitly assumes that one of the major effects of the various structural substituents so far studied is a reduction in the frequency of trans-gauche isomerization in the hydrocarbon chains, with the result that the liquid-crystalline states of such bilayers are, at comparable temperatures relative to their respective gel/liquid-crystalline phase transition temperatures, somewhat more ordered than bilayers composed of unsubstituted acyl chains.…”
Section: Discussionmentioning
confidence: 73%
“…It is possible that the specific effects of acyl chain structure on the La/Hn transition to PEs (i.e., those effects not attributable to changes in acyl chain length and the L8/La phase transition temperature) may be attributable to small differences in the packing energy of the chains and/or to differences in the temperature-dependent changes in the dynamic properties of the liquid-crystalline lipid bilayer. It has been shown previously that acyl chain substitutions of the types described in these studies can have significant effects on the packing properties of the liquid-crystalline state of lipid bilayers (MacDonald et al, 1983(MacDonald et al, , 1984(MacDonald et al, , 1985aSuzuki & Cadenhead, 1985; Rice et al, 1987;Balthasar et al, 1988). In fact, the interpretation of such data implicitly assumes that one of the major effects of the various structural substituents so far studied is a reduction in the frequency of trans-gauche isomerization in the hydrocarbon chains, with the result that the liquid-crystalline states of such bilayers are, at comparable temperatures relative to their respective gel/liquid-crystalline phase transition temperatures, somewhat more ordered than bilayers composed of unsubstituted acyl chains.…”
Section: Discussionmentioning
confidence: 73%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] For example, the main transition temperature (from P b -L a liquid-crystalline phase) can be varied in response to changes in the environment by three major processes: (i) shortening of fatty acid acyl chain length; (ii) increasing ratio of saturated relative to unsaturated fatty acid chains; and (iii) increasing the fraction of ante-iso branched chains by simultaneously decreasing the fraction of iso branched fatty acid chain. 9,10,[23][24][25] For example Listeria monocytogenes, a foodborne pathogenic bacterium (which is often lethal), is capable of growing in household fridges (around 283 K). 26 Simply stated, it retains its membrane in a functional, liquid-crystalline state by reducing the ratio between iso to ante-iso fatty acids, as well as shortening the length of the membrane lipids.…”
Section: Introductionmentioning
confidence: 99%
“…Shabala et al showed that in cfa -deletion mutations, E. coli increased proton permeability and reduced the ability to excrete H + and they confirmed that cfa can protect E. coli from acid stress by reducing cell membrane permeability to H + 29. Macdonald et al have confirmed that an increase in cfa leads to an increase in cell membrane stability and rigidity, and an increase in cell membrane rigidity is associated with a decrease in proton permeability 30. Studies have shown that the decrease of cell membrane permeability of bacteria will lead to the decrease the concentration of antibiotics entering biofilms , the slow growth of bacteria, which will lead to bacterial tolerance to antibiotics 3133.…”
Section: Discussionmentioning
confidence: 95%